(untitled) (International Journal of Engineering and Computer Science, 2017)
Location-based services (LBS) are information and entertainment services that are accessible by mobile users through mobile networks. Examples of LBS are: Location-based traffic reports like how many cars in the free way, what is the estimated travel time to reach my destination; Location-based store finder like what are the restaurants within five miles of my location, where is my nearest fast food restaurant; Location-based advertisement like sending E-coupons to all customers within five miles of my store etc. LBS rely mainly on an implicit assumption that mobile users are willing to reveal their private locations. With untrustworthy LBS providers, the revealed private location information could be abused by adversaries. For example, an adversary may infer a user’s medical record by knowing that she regularly visits a specialized clinic. Recently, there is huge interest to enable privacy-preserving LBS in which users can entertain high quality location-based services without compromising their privacy. In this paper we will discuss LBS architecture and research issues. In first section, we discuss primary concepts and different architecture of LBS. In second section we discuss research challenges and scopes.